Relação entre organizações e a construção do ambiente legal do sistema de identificação civil brasileiro - Carneiro, Thaís Gualda (2012)
The aim of this dissertation is to understand how the articulation of social actors, public and private, influenciated the process of social construction of Federal Law 9454, establishing the unique register of Brazilian civil identification, in the period of 1997 to 2011. The work justifies itself theoretically by rescuing the normative aspect as a relevant variable to the analysis of the relationship between law and organizations and to emphasize the active role of organizations in building the sense of legality, affecting interpretations about the meanings of the law and modes of compliance, emphasizing the dynamic character of the legal environment. The practical justification is the fact that the object of study allows the analysis of how social actors, public and private, articulated themselves to defend their interests, allowing the identification of areas of exchange and bargaining along the process, as well as tactics used by them to influence the regulatory system. Also to analyze the participation of private organizations in the public sphere, allowing reflection on the mechanisms used by the private sector to influence the process of construction of government policies. In this work the deterministic character of the relationship between laws and organizational behavior is challenged, recognizing that statutory law does not imply the coincidence between reality and rule (HESSE, 1991), allowing differentiation between legal validity and social validity by discussing the intermediate process of social construction of the legal environment, through the articulation of incumbent actors (EDELMAN e SUCHMAN, 1997; EDELMAN, UGGEN e ERLANGER, 1999; FLIGSTEIN, 2008; SCOTT, 2008). The articulation of social actors was analyzed by discursive strategies of framing and also by the mobilization of material and relational recourses, assuming that the discursive strategies serve as a resource for creating, maintaining or challenging concepts that linked to material and relational resources can explain the dynamics of the process of structuring legal environment (LAWRENCE e SUDDABY 2006). In order to achieve the objectives outlined, the institutional perspective was adopted as it recognizes the duality of social structure, represented by the interdependence of material and ideational aspects (SCOTT, 2008). This case adopted a qualitative and descriptive nature with longitudinal evaluation, although supported by interviews with sectional character. The study allowed the analysis of the relationship between laws and organizations such as codependent and not dichotomous (CRUBELLATE, MENDES e JÚNIOR, 2009) as the notion of legality served as a symbolic indicator of social conformity (TALESH, 2009) and subsidized different types of responses to the law, causing changes in parameters previously institutionalized and serving as a legitimate motivation to confront and oppose other laws already in social validity (DOBBIN e SUTTON, 1998; EDELMAN, 1990; KAGAN, GUNNINGHAM e THORNTON, 2003; HAWKINS, 1983). It also allowed the analysis of the social construction of the legal environment as a process of structuring concepts relating to law, the legality and the modes of legitimate action.